CONCEPTUAL DIRECTIONS FOR ORGANIZING A BANK AUDIT ON THE BASIS OF INTERNATIONAL AUDITING STANDARDS (International Congress on Economics, Management and Business Studies, 2026)
The thesis examines the conceptual directions of organizing a bank audit based on international auditing standards (IAS). The conceptual model of a bank audit is characterized as a combination of risk sensitivity, regulatory compliance, and information value.
Keywords: International auditing standards, bank auditing, conceptual areas, risk-based auditing, prudential supervision, audit quality, information value, regulatory compliance, ISA 250, ISA 540.